(untitled) (Revista Latino-Americana de Enfermagem, 2000)
Through the participant-research framework, this collective study was carried out by a group of faculty nurses responsible for the course of Nursing Fundamentals at Londrina State University. Considering the discussion that emerged from the participative process and based on the Historical-Critical Pedagogy, the most relevant concepts and pedagogic practices were selected, through the presentation and discussion of the following categories: Goals, Contents, Methodology and Evaluation. Authors concluded that the reflections emerged by and with the group about pedagogic aspects effected the performance of the involved faculty as well as that the collective process must be continuous in order to support the pedagogic development of these professionals, who are educational agents concerned with the improvement of nurses' formation.